Emergency nursing assessment and care in Crohn's disease: a student case study of an osteoporosis-related hip fracture. (2nd November 2020) - Fraser, Ruth; Baker, Mark J
Abstract : Crohn's disease is a long-term, painful inflammatory condition that may affect any or all parts of a person's gastrointestinal tract and is categorised under the umbrella term of inflammatory bowel disease. The exact aetiology is unclear, although a range of factors are thought to be responsible. Pharmacological interventions used to manage active Crohn's disease, such as steroids, can have a detrimental effect on the patient's bone density, leading to complications, such as osteoporosis, and subsequent bone fractures following minor trauma. A case study is presented of a patient with Crohn's disease who presented to the emergency department with a hip fracture, likely caused by osteoporosis due to a history of steroid use to manage his Crohn's disease. The case study illustrates a holistic, patient-centred approach to nursing assessment, management and evaluation of care, demonstrated by a student nurse under the supervision of a qualified nurse. It shows how nursing practice should be guided by reliable and credible evidence to ensure continuity of care and the best possible outcomes for patients, as well as ensure that the patient's psychological wellbeing, as well as their physical health, is cared for.